Concomitant Occurrence of Transmissible Venereal Tumor, Pyometra, and Pregnancy with Cleft Lip and Palate in a Crossbreed Bitch: A Case Report (Indonesia Medicus Veterinus, 2022)
A female crossbreed dog, estimated to be four years old with a bodyweight of 9.5 kg was diagnosed with a transmissible venereal tumor (TVT). Cytological examination showed the shape of lymphocytic and plasmacytic cells which are consistent with the transmissible venereal tumor cell findings. Treatment was done by en bloc ovariohysterectomy, surgical excision of the tumor mass, and chemotherapy using vincristine sulfate. During the surgery, it was found that apart from being infected with TVT, the dog was also observed with pyometra and found to be pregnant. The dog had one puppy with a birth defect (cleft lip and palate) and died a few hours later. Postoperatively, dogs were given a combination of dexamethasone and diphenhydramine (0.2 mg/kg BW and 4 mg/kg BW intramuscularly/IM) and antibiotic cefotaxime (22 mg/kg q12h IM). Two days after the surgery the dog showed an improvement in its condition, oral drugs began to be administered and injection drugs were stopped. Treatment was continued with the administration of antibiotic cefadroxil (22 mg/kg BW q12h per orally/PO) and metronidazole (15 mg/kg q12h PO) for five days along with the administration of multivitamin Nutrilite Double X-Phytonutrient® one capsule/day for seven days. A week after surgery the dog was sent home without additional medication. The dog is scheduled for chemotherapy the following week.